Shaxs psixologiyasında stress mashqalası - Dawkeeva, A; Saidaxmetova, Х (SCIENCE and SOCIETY, 2025)
The development of neuropsychiatric diseases associated with the physical state of the stressor, as well as the effects of various types of stress, is discussed.
Keywords: stress; psychological stress; distress; message stress; emotional stress; frustration; discomfort; mental stress